Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan UMKM Batik Di Kota Surakarta Tahun 2015-2019 - Tiya Ratna Sari; Achma Hendra Setiawan (BISECER (Business Economic Entrepreneurship), 2022)
The city of Surakarta is well known to the public as a city with a center for batik, where batik is one of the leading products in the city of Surakarta. Most of the people earn income from batik. The income of Batik SMEs during the last two years has decreased significantly, this can be influenced by various factors. This study aims to determine and analyze the effect of capital, labor and education on the income of Batik SMEs in Surakarta City.This research is a type of quantitative research. The sample used in this study were 80 respondents using purposive sampling technique. The data used is primary data based on a questionnaire. The analysis technique used is multiple linear regression with income as the dependent variable and three independent variables, namely capital, labor and education.The results of this study indicate that there is a positive and significant effect of capital, labor and education on the income of Batik SMEs in Surakarta City. The independent variables jointly affect the income of Batik SMEs in Surakarta City. The dominant variable that influences the income of Batik Center UMKM in Surakarta City is the capital variable..